Pengaruh Afiliasi KAP Big Four dan Komite Audit Terhadap Integritas Laporan Keuangan - Farrel Rasya Agrapana; Erry Andhaniwati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to test and analyze the effect of the Big Four KAP affiliation and the audit committee on the integrity of financial statements. The population used is all companies listed on the Indonesia Stock Exchange for the period 2020-2023, with a total sample of 43 companies. The test method uses Partial Least Square (PLS) which is processed with SmartPLS Version 3.0. The results showed that the audit committee had an effect on the integrity of financial statements and the Big Four KAP affiliation had no effect on the integrity of financial statements.